Strengthening Ethical Competence in Digital Communication Among Students in West Kalimantan - Aunurrahman Aunurrahman (JETL (Journal of Education, Teaching and Learning), 2025)
This research fundamentally aims to understand and describe the strengthening of ethical competence in digital communication among students in West Kalimantan. Based on the background review and analysis presented, the approach and method used in this study is a quantitative approach through a survey study, by distributing questionnaires to teachers in various districts/cities in West Kalimantan. The data obtained is collected and analyzed using statistical formulas, then presented in the form of tables, diagrams, or graphs to provide ease for readers in understanding the meaning of the data presented.The study concludes that: (1) strengthening ethical competence should be an integral part of the overall school program. Specific guidance from teachers in students' digital communication is highly needed; (2) strengthening ethical competence has several positive elements, particularly in fostering comfortable communication and a conducive learning environment that enables better interaction between students and teachers, as well as among students themselves; (3) strengthening ethical competence in digital communication for students covers several fundamental aspects, particularly regarding etiquette and the way to express gratitude in communication processes, initiating conversations, expressing ideas, or conveying information or thoughts in communication; (4) an evaluation of strengthening students' ethical competence in digital communication needs to be conducted, especially by involving all school elements, particularly teachers and school staff.